2020
DOI: 10.3390/ijms21207504
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Response and Immune Defense

Abstract: DNA damage is the cause of numerous human pathologies including cancer, premature aging, and chronic inflammatory conditions. The DNA damage response (DDR), in turn, coordinates DNA damage checkpoint activation and promotes the removal of DNA lesions. In recent years, several studies have shown how the DDR and the immune system are tightly connected, revealing an important crosstalk between the two of them. This interesting interplay has opened up new perspectives in clinical studies for immunological diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 199 publications
1
45
0
3
Order By: Relevance
“…Consistent with previous reports BRCA mutations in breast cancer were mostly associated with regulation of cell cycle, DNA damage, and cell proliferation in breast cancer [ 71 ], and with immune system-related processes in ovarian cancer [ 61 ], which may be an indicator of differential role of BRCA1 and BRCA2 in the pathogenesis of these diseases. Previous studies have already suggested mechanisms of how DNA damage may trigger immune response [ 72 , 73 ]; however, the question of why its intensity is higher in ovarian rather than in breast cancer remains open.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous reports BRCA mutations in breast cancer were mostly associated with regulation of cell cycle, DNA damage, and cell proliferation in breast cancer [ 71 ], and with immune system-related processes in ovarian cancer [ 61 ], which may be an indicator of differential role of BRCA1 and BRCA2 in the pathogenesis of these diseases. Previous studies have already suggested mechanisms of how DNA damage may trigger immune response [ 72 , 73 ]; however, the question of why its intensity is higher in ovarian rather than in breast cancer remains open.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the DDR pathway contains eight sub-pathways that can be divided into two main mechanisms. The pathways initiated in response to single-stranded DNA damage include base excision repair (BER), nucleotide excision repair (NER), mismatch repair (MMR), and single-stranded DNA binding (SSB), while the pathways activated during doublestranded DNA damage include nonhomologous end joining (NHEJ), homologous recombination (HR), the Fanconi anemia (FA) pathway and double-strand break repair (DSB) (13)(14)(15). All of the sub-pathways above are connected to each other to form a network that induces the DDR pathway in response to DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…The prominent role of ATM is in DDR [54], especially in the DSBR mechanism and cell redox balance. In A-T, the activation of microglia and neurotoxic cytokine secretion are caused by the accumulation of cytoplasmic single stranded/double stranded self-DNA which is recognized by the innate immune system due to DNA repair defects [118,119]. Recent studies give insight into this issue.…”
Section: A-tmentioning
confidence: 99%